Students' and Teachers' Perceptions on the Implementation of Contextual Learning Based on Local Potential: A Case Study of Economic Geography in Cirebon Regency - Pratiwi, Rahayuni Tyas; Ningrum, Epon; Triana, Igna Juli (Universitas Pendidikan Indonesia, 2025)
This study aims to describe how the implementation of contextual learning based on local potential, as well as describe the perception of students and teachers in Cirebon Regency. The method used is quantitative descriptive. The data collection technique was carried out through the distribution of questionnaires for students and teachers for several schools that are close to local potential sources such as the batik and Trusmi industry, pottery businesses, salt ponds, and leather cracker businesses. The results of the study showed that students had a high interest in contextual learning based on local potential. the impact of contextual learning of real life is 39% students strongly agree and 65% students agree. And teachers' perception of contextual learning in geography, as many as 91% of teachers have a good understanding of the basic principles of the contextual approach. In addition, 92% of teachers believe that contextual learning can improve students' understanding of geography subjects. Some schools supported by institutions have implemented contextual learning processes based on local potential. However, on the other hand, this study shows that there are obstacles in the contextual learning process. Among them are time constraints, and support from schools. This study concludes that contextual learning based on local potential has a positive impact on improving the meaning and quality of geography learning. As well as being able to increase students' love for their respective regions. Therefore, teacher training and sustainable education policies are needed to support the integration of local potential into the learning curriculum.